If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 7 = 15x + -14 Reorder the terms: 7 + 12x = 15x + -14 Reorder the terms: 7 + 12x = -14 + 15x Solving 7 + 12x = -14 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 7 + 12x + -15x = -14 + 15x + -15x Combine like terms: 12x + -15x = -3x 7 + -3x = -14 + 15x + -15x Combine like terms: 15x + -15x = 0 7 + -3x = -14 + 0 7 + -3x = -14 Add '-7' to each side of the equation. 7 + -7 + -3x = -14 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -14 + -7 -3x = -14 + -7 Combine like terms: -14 + -7 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| 3x=288x | | N-7=3+2n | | 2x+1=5x-44 | | f(x)=(6+4x+3x^2)*(2+4x+2x^2) | | -5=3x-29/4 | | 5v^2+44v+32=0 | | 4(-1+4)=12 | | y=6(3)-39 | | x-3=-5x-9 | | (2k+3)(5k+1)= | | 9+5w-1w=12-6w | | 10m^2-53m+36=0 | | 7x+2x-3x=3(x-8) | | y=2(3)-25 | | .01(900-30x)=9.8x+400 | | 3x^2=288x^2 | | 9+5w-14x=12-6w | | y=3(3)-22 | | 5(2x+6)=4(-5-2x)3x | | x-4=-4x-2 | | 4m-19-11=70 | | 6r-18=30 | | 18=-3y-12 | | 87-x=136 | | 3/8=r2/3 | | (3w+5x-7)(w+7x)= | | X+5=x+11 | | 5x+4x+8-2x-8= | | 4/17 | | y=-5(3)+17 | | 2=(4/p) | | 4(6-4+6)= |